2021
DOI: 10.20448/801.61.39.46
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Gadget in Speaking Arabic as a Foreign Language During the Covid 19

Abstract: In the 4th Industrial Revolution (IR 4.0) era, learning a foreign language including Arabic has continued to become challenging for non-native speakers besides it has been identified as one of the difficult foreign languages around the world, according to the UNESCO report. To overcome this, the contemporary Arabic language students are practically being engaged with different technological gadgets in mastering the language. Nevertheless, the story is different for students facing connectivity and technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…So the field of foreign language teaching which has witnessed a tremendous increase in the use of drama in different contexts (Fleming, 2018). Drama is helpful for the development of learners' language skills (Maley & Duff, 2005;Mokhtar, 2021;Paley, 1990;Ulas, 2008;Zakarneh & Mahmoud, 2021). Especially, Maley and Duff (2005) noted that drama naturally integrates language skills and harmonizes verbal and nonverbal aspects of communication.…”
Section: Drama Technique In Efl Classroomsmentioning
confidence: 99%
“…So the field of foreign language teaching which has witnessed a tremendous increase in the use of drama in different contexts (Fleming, 2018). Drama is helpful for the development of learners' language skills (Maley & Duff, 2005;Mokhtar, 2021;Paley, 1990;Ulas, 2008;Zakarneh & Mahmoud, 2021). Especially, Maley and Duff (2005) noted that drama naturally integrates language skills and harmonizes verbal and nonverbal aspects of communication.…”
Section: Drama Technique In Efl Classroomsmentioning
confidence: 99%
“…Ismail et al (2020) reported the results to indicate that Arabic-speaking anxiety among secondary religious school students in Malaysia is moderately high. Researchers such as Mokhtar (2021) said that Arabic is the most difficult foreign language and triggers anxiety among learners, especially in speaking skills. Nevertheless, according to (Haron, 2021), many findings showed that the outbreak of the COVID-19 pandemic in 2020 has caused a significant transformation in the education system entire world.…”
Section: Arabic Language In Malaysiamentioning
confidence: 99%
“…In this era characterized by information abundance and rapid technological advancements, the ability to communicate, educate, and entertain effectively in the Arabic language is essential (Mokhtar, 2021). This underscores the critical need to explore and harness the potential of Arabic multimedia and gamification comprehensively (Al-Kwai et al, 2014;Sulistianingsih & Mukminan, 2019).…”
Section: Introductionmentioning
confidence: 99%